2012
DOI: 10.1111/j.1600-051x.2012.01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex I virus impairs regenerative outcomes of periodontal regenerative therapy in intrabony defects. A pilot study

Abstract: The presence of herpesvirus-1 at baseline is associated with poor clinical outcomes following regenerative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“… showed that periodontal herpes simplex virus type 1 impaired clinical outcomes of regenerative therapy. The clinical attachment level improved by 5.9 ± 1.9 mm in herpes simplex virus type 1‐negative sites but only by 0.2 ± 1.8 mm in herpes simplex virus type 1‐positive sites, and gingival recession increased by 0.3 ± 0.7 mm in herpes simplex virus type 1‐negative sites but by as much as 3.0 ± 1.6 mm in herpes simplex virus type 1‐positive sites . Case reports have also related a herpes simplex virus type 1 infection to severe gingival inflammation and recession after muco‐gingival therapy .…”
Section: Disease Associationsmentioning
confidence: 99%
“… showed that periodontal herpes simplex virus type 1 impaired clinical outcomes of regenerative therapy. The clinical attachment level improved by 5.9 ± 1.9 mm in herpes simplex virus type 1‐negative sites but only by 0.2 ± 1.8 mm in herpes simplex virus type 1‐positive sites, and gingival recession increased by 0.3 ± 0.7 mm in herpes simplex virus type 1‐negative sites but by as much as 3.0 ± 1.6 mm in herpes simplex virus type 1‐positive sites . Case reports have also related a herpes simplex virus type 1 infection to severe gingival inflammation and recession after muco‐gingival therapy .…”
Section: Disease Associationsmentioning
confidence: 99%
“…However, the considerable heterogeneity of the literature on study populations, sample sizes, onset and duration of diabetes, level of glycemic control, and diagnosis of periodontal disease does not allow any easy discrimination. [27,[64][65][66][67] Chronic hyperglycemia is one of the key features of diabetes mellitus, but its effect on periodontal disease is much less known than the effects of diabetes, [19,68] particularly on the influence of IGT or IGF on periodontitis. Periodontal diseases can also play a role in cytokine mediation as an inflammatory condition.…”
Section: Number Of Cigarettes Per Daymentioning
confidence: 99%
“…The connective tissue inflammation recorded resulted in significantly higher gingiva close to restorations than that in the gingiva close to the unrestored defects. In our study, we considered healthy patients, not suffering from periodontal disease (which is an inflammatory disease due to a systemic hindered control of inflammatory challenges), nonsmokers, with high compliance, to be subjected to a stringent supportive therapy (Bertoldi et al, 2012(Bertoldi et al, , 2013Page & Eke, 2007). The composite resin used was accurately managed, with respect to the preparation, bonding, high adaptation of margin, finishing and polishing, and also to control surface roughness.…”
Section: Discussionmentioning
confidence: 99%